POLITENESS STRATEGIES USED BY DONALD TRUMP AND JOE BIDEN IN THE U.S. 2020 FINAL PRESIDENTIAL DEBATE - Putri, Nadia Rafika; Ekawati, Rosyida (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2023)
This study aims at determining the types of politeness strategies used by and the sociological variables influencing the candidates, Donald Trump and Joe Biden, in the U.S. 2020 Final Presidential Debate. This study also used the theory of Brown and Levinson (1987). This study used the U.S. 2020 final presidential debate video as the source of data. The video was uploaded on YouTube on October 22, 2020. The data were the speaker’s utterances containing politeness strategies. The results of the study revealed that the two candidates used various politeness strategies in the debate. There were 42 data obtained from the statements of the candidates who used the politeness strategy. The most widely used strategy by the two candidates is positive politeness. Then, negative politeness, off record, and bald on record respectively. Meanwhile, the use of politeness strategy by the candidates is influenced by social distance (D) and absolute ranking (R) of impositions.